1976
DOI: 10.1139/b76-113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of seed dormancy in Elaeagnus angustifolia by endogenous growth substances

Abstract: A coumarin-like germination inhibitor was found in the endocarp, testa, and embryo of dormant seed of Elaeagnus angustifolia L. Activity of the inhibitor did not decrease during 90 days at 5 °C. However, evidence showed that the inhibiting substance may be physiologically effective in preventing germination of dormant seed. A growth-promoting substance formed during low-temperature afterripening apparently reverses the effect of the endogenous inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Russian olive seeds generally exhibit embryonic dormancy and require a period of cold stratification for germination Olson 1974;Hamilton and Carpenter 1976). Field observations indicated that both vegetative and flower bud-break occurred near the southern limit in 2009 (Guilbault, personal observation).…”
Section: Russian Olive Is Now One Of the Dominant Woody Plants Along mentioning
confidence: 99%
See 1 more Smart Citation
“…Russian olive seeds generally exhibit embryonic dormancy and require a period of cold stratification for germination Olson 1974;Hamilton and Carpenter 1976). Field observations indicated that both vegetative and flower bud-break occurred near the southern limit in 2009 (Guilbault, personal observation).…”
Section: Russian Olive Is Now One Of the Dominant Woody Plants Along mentioning
confidence: 99%
“…However, the effect of germination inhibitors in the inner and outer seed coatings and embryo Hamilton and Carpenter 1976) may be more limiting than the physical structure of the seed coat itself because the seed coat of Russian olive seeds was not found to prevent water uptake-although it may limit gas exchange . The natural scarifying agents of Russian olive seeds are bird guts, river-bed sediment and freeze-thaw cycles.…”
Section: Germination and Stratification Thermal Time Unitsmentioning
confidence: 99%
“…Milborrow (1967) regarded abscisic acid as the main component of the |8-inhibitor. However, this is not the only inhibiting substance, as several phenolic acids and coumarins were also detected in samples taken froni fruits (Varga 1957), tubers (Hoist 1971, Sanchez-Tames et al 1973, seeds (Hamilton and Carpenter 1976) and dormant buds (Thakur 1977). As dormancy proceeds towards budbreak, the level of abscisic acid declines in buds of Prunus cerasus (Mielke and Dennis 1975), Betula verrucosa (Harrison and Saunders 1975), Prunus persica (Corgan and Martin 1975), Fagus sylvatica and Ribes nigrum (Wright 1975), Maltis domestica (Seeley and Powell 1981) and Carya illinoensis (Wood 1983), Endogenous levels of growth promoters, such as auxins, also change during the period preceding budbreak (Bennet andSkoog 1938, Wood 1983),…”
Section: Introductionmentioning
confidence: 97%
“…Seeds of oleaster were broken out of physiological dormancy by storing at low temperature for 90 days -upon which coumarin, a germination catalyst started to be created (Hamilton and Carpenter, 1975). Seeds of Pinus taeda saw the concentration of germination catalysts increase over the course of 42 days at low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton and Carpenter (1975) used oleaster seeds to confirm that storing them at 5℃ for 90 days causes germination promoting substance to be created. Furthermore, this catalysts broke physiological dormancy caused by a germination retardant in coumarin, and also Paul et al (1973) reported that storing Pinus taeda seeds in tiers at 5℃ for 42 days caused the catalysts to increase while reducing concentration of the retardant close to zero.…”
Section: Introductionmentioning
confidence: 99%